ENGLISH-ACHIEVING THE TRUE PURPOSE OF EDUCATION: ROLE OF CURRENT SYSTEM OF EDUCATION AND ISLAMIC VIEWPOINT - Aziz-ur-Rehman Saifee; Nasir Majeed; Qari Badaruddin (دی اسکالر)
The study will highlight the core problems of a society that arise with the deficiency of a proper mode of education. Also, this research will emphasize the problems associated with the improper implementation of the current system of education and those that the current system has failed to encounter. It will provide an Islamic perspective in the light of the achievements it has had in the construction of a society in the past with emphasis laid on the background of those societies. The thesis will also highlight the aspects of application of Islamic ideas to a true purpose of education and its feasibility for the environment of the present day society and its pace of modernization. The research will be based on qualitative approach listing the facts to reach a conclusion. Previous thesis, relevant books, expert opinions and internet researches will be used to gather the facts in the process of this study. The qualitative scheme is preferred over the quantitative as the amount of knowledge about the Islamic ideology in general public, in devising an opinion about the Islamic motives, is questionable. Therefore, any conclusion formulated on the basis of the information collected from the surveys and opinion polls will be highly unjustified.